1986
DOI: 10.1128/aem.51.5.1089-1098.1986
|View full text |Cite
|
Sign up to set email alerts
|

Alginate Beads as Synthetic Inoculant Carriers for Slow Release of Bacteria That Affect Plant Growth

Abstract: Uniform synthetic beads were developed as carriers for the bacterial inoculation of plants. The beads are made of sodium alginate and skim milk and contain a large reservoir of bacterial culture which releases the bacteria at a slow and constant rate. The beads are biodegradable and produce no environmental pollution. The strength of the beads, the rate of bacterial release, and the time of their survival in the soil can be controlled by several hardening treatments. The final product, lyophilized beads, is si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
106
0
4

Year Published

1988
1988
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(120 citation statements)
references
References 25 publications
3
106
0
4
Order By: Relevance
“…However. Bashan (1986) found that high numbers of cells of .izospirillum brasilense could be released from alginate beads within 24 h. In our first experiment with tomato cuttings, isolate 529 did not infect when incorporated in the gel applied to wounds, whereas with carrot discs good infection was achieved with isolate T37 applied in the gel This aspect merits further study with a view to combining gel protection with an appropriate delivery system for bacterial inoculants.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…However. Bashan (1986) found that high numbers of cells of .izospirillum brasilense could be released from alginate beads within 24 h. In our first experiment with tomato cuttings, isolate 529 did not infect when incorporated in the gel applied to wounds, whereas with carrot discs good infection was achieved with isolate T37 applied in the gel This aspect merits further study with a view to combining gel protection with an appropriate delivery system for bacterial inoculants.…”
Section: Discussionmentioning
confidence: 71%
“…1986). There are no previous reports of the production of calcium alginate gels in situ on roots or stem bases, although sodium alginate is marketed for application to roots of transplants to help prevent desiccation, and preformed calcium alginate beads have been used by several workers as a means of delivering microbial inocula into soil (Walker & Connick, 1983;Fravel et ai, 1985;Bashan, 1986;.…”
Section: Discussionmentioning
confidence: 99%
“…These environments may also be toxic or too oligotrophic to support growth or maintenance requirements of the added cells (Crawford et al 1989). The use of an alginate matrix to immobilize live strains of micro-organisms has been reported (Bashan 1986;Crawford et al 1989;Trevors et al 1993;Hall et al 1998), and the technology has been used to apply microorganisms into hostile environments and provide nutrients and appropriate conditions to allow them to perform their intended task (Cassidy et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Encapsulated bacteria are a safe and useful way to apply inoculants to soil environments in agriculture [20,21] and soil bioremediation [22,23]. During the early 1990s, reviews were published on methods of introducing bacteria into soil [24] and the use of solid carriers to introduce bacteria into soil [25].…”
Section: Introductionmentioning
confidence: 99%